2021
DOI: 10.1038/s41598-021-01587-7
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative transcriptomic profiling of susceptible and resistant cultivars of pigeonpea demonstrates early molecular responses during Fusarium udum infection

Abstract: Vascular wilt caused by Fusarium udum Butler is the most important disease of pigeonpea throughout the world. F. udum isolate MTCC 2204 (M1) inoculated pigeonpea plants of susceptible (ICP 2376) and resistant (ICP 8863) cultivars were taken at invasion stage of pathogenesis process for transcriptomic profiling to understand defense signaling reactions that interplay at early stage of this plant–pathogen encounter. Differential transcriptomic profiles were generated through cDNA-AFLP from M1 inoculated resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 70 publications
(107 reference statements)
0
4
0
Order By: Relevance
“…Seeds of wilt-susceptible ICP 2376 and wilt-resistant ICP 8863 cultivars were collected from International Crops Research Institute for the Semi-Arid Tropics (ICRISAT), Hyderabad, Telangana, India. After surface sterilization of seeds, susceptible and resistant seedlings were grown in soilrite at 22–25°C, 35%–40% humidity, and a 16-h photoperiod ( Purohit et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seeds of wilt-susceptible ICP 2376 and wilt-resistant ICP 8863 cultivars were collected from International Crops Research Institute for the Semi-Arid Tropics (ICRISAT), Hyderabad, Telangana, India. After surface sterilization of seeds, susceptible and resistant seedlings were grown in soilrite at 22–25°C, 35%–40% humidity, and a 16-h photoperiod ( Purohit et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of our previous report, it was found that at the early stage of F. udum infection, maximum disease-responsive pathways were altered in pigeonpea ( Purohit et al, 2021 ). Accordingly, the present study was designed to perform NGS-based comparative transcriptomic profiling of F. udum -induced transcripts at the early (36 HPI) infection stage in pigeonpea through an RNA-seq technique to accomplish a thorough understanding of the differentially expressed genes.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Fusarium spp. is a soil-borne pathogen that mainly overwinters in the form of mycelia and spores in diseased residues, infected seeds, and soil [17]. Fusarium spp.…”
Section: Introductionmentioning
confidence: 99%